In the “Crossfire” of the acquisition process: Exploring middle managers’ unfolding mediation dynamics - Birollo Gustavo; Rouleau Linda; Teerikangas Satu (Elsevier, 2025)
This study addresses middle managers, a relatively unexplored actor type in the merger and acquisition literature. Building on the mediation metaphor, we explore both acquired and acquiring middle managers throughout the acquisition process. Based on 52 semi-structured interviews, we advance our knowledge of the dynamics of the mediation roles of acquired and acquiring middle managers in the unfolding stages of the acquisition process. Notably, middle managers engage in mediation at three levels—self-mediation, interfirm mediation and stakeholder mediation—which, when combined, create specific mediation dynamics during each acquisition stage. Consequently, the pre-acquisition stage is characterised by cold mediation, the approval stage by informal mediation, the first post-acquisition phase by disrupted mediation and a potential second post-acquisition phase by joint mediation. The main contribution of the paper is in conceptualising middle managers’ mediation roles and the resulting mediation dynamics throughout the acquisition process. Essentially, middle managers are not only intermediaries transferring meanings across organisations but also mediators transforming and adapting the meanings that flow between both organisations, thereby shaping the course of the acquisition process. The paper thus sheds light on the important role of middle managers in facilitating the acquisition process.